If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4)(x + -6) = -21 Reorder the terms: (-4 + x)(x + -6) = -21 Reorder the terms: (-4 + x)(-6 + x) = -21 Multiply (-4 + x) * (-6 + x) (-4(-6 + x) + x(-6 + x)) = -21 ((-6 * -4 + x * -4) + x(-6 + x)) = -21 ((24 + -4x) + x(-6 + x)) = -21 (24 + -4x + (-6 * x + x * x)) = -21 (24 + -4x + (-6x + x2)) = -21 Combine like terms: -4x + -6x = -10x (24 + -10x + x2) = -21 Solving 24 + -10x + x2 = -21 Solving for variable 'x'. Reorder the terms: 24 + 21 + -10x + x2 = -21 + 21 Combine like terms: 24 + 21 = 45 45 + -10x + x2 = -21 + 21 Combine like terms: -21 + 21 = 0 45 + -10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-45' to each side of the equation. 45 + -10x + -45 + x2 = 0 + -45 Reorder the terms: 45 + -45 + -10x + x2 = 0 + -45 Combine like terms: 45 + -45 = 0 0 + -10x + x2 = 0 + -45 -10x + x2 = 0 + -45 Combine like terms: 0 + -45 = -45 -10x + x2 = -45 The x term is -10x. Take half its coefficient (-5). Square it (25) and add it to both sides. Add '25' to each side of the equation. -10x + 25 + x2 = -45 + 25 Reorder the terms: 25 + -10x + x2 = -45 + 25 Combine like terms: -45 + 25 = -20 25 + -10x + x2 = -20 Factor a perfect square on the left side: (x + -5)(x + -5) = -20 Can't calculate square root of the right side. The solution to this equation could not be determined.
| -13+(-4)(-2)= | | w^2-8w=20 | | 29x^2-7=0 | | .02(2c-24)=-0.4(c-1) | | 5a+3(8-a)=36 | | -97=-6x+11 | | (x+4)(x+6)+21=0 | | (x+4)(x+6)=-21 | | x+2=3-2x+8 | | -4c+4+2c=3c-16 | | 10x^2-3x-13=0 | | -m+1=14 | | 12b^4+3b= | | 2+3y-4=5y+6 | | 4x^2=2+2x | | 3x+2-5x=-x+3 | | x^2+2x-195=0 | | (4u+2)(7-u)=0 | | -8p-5=91 | | 32=8+6b | | 10n=20 | | -5-11=14 | | 54(15)=15(75)+3(2)(d) | | 9=3k+9 | | 3(x-1)=11 | | 45-t=30 | | x-4(4+2c)=0 | | -3(w+2)(-w+1)=0 | | 3c-(4+2c)=0 | | 3(g-5)+8g=18-(3-10g) | | 3c-4(4+2c)=0 | | 3-2(2x-3)=17 |